Wokół Władzy (i nie tylko). Kilka listów Tadeusza Konwickiego (z komentarzem) - Smulski, Jerzy (Śląskie Studia Polonistyczne, 2020)
The article contains a discussion of the author’s correspondence with Tadeusz Konwicki pertaining to socialist realism in literature, particularly to the latter’s novel Władza. Thus far unpublished Tadeusz Konwicki’s letters are quoted here in their entirety.